Haustorial Hairs Are Specialized Root Hairs That Support Parasitism in the Facultative Parasitic Plant Phtheirospermum japonicum . Issue 3 (28th December 2015) - Cui, Songkui; Wakatake, Takanori; Hashimoto, Kei; Saucet, Simon B.; Toyooka, Kiminori; Yoshida, Satoko; Shirasu, Ken
Abstract : Isolation and analysis of parasitic plant mutants with defects in haustorial hair development shows that these specialized root hairs are important for tight interactions with the host plant roots. Abstract: A haustorium is the unique organ that invades host tissues and establishes vascular connections. Haustorium formation is a key event in parasitism, but its underlying molecular basis is largely unknown. Here, we use Phtheirospermum japonicum, a facultative root parasite in the Orobanchaceae, as a model parasitic plant. We performed a forward genetic screen to identify mutants with altered haustorial morphologies. The development of the haustorium in P. japonicum is induced by host-derived compounds such as 2, 6-dimethoxy- p -benzoquinone. After receiving the signal, the parasite root starts to swell to develop a haustorium, and haustorial hairs proliferate to densely cover the haustorium surface. We isolated mutants that show defects in haustorial hair formation and named them haustorial hair defective ( hhd ) mutants. The hhd mutants are also defective in root hair formation, indicating that haustorial hair formation is controlled by the root hair development program. The internal structures of the haustoria in the hhd mutants are similar to those of the wild type, indicating that the haustorial hairs are not essential for host invasion. However, all the hhd mutants form fewer haustoria than the wild type upon infection of the host roots. The number of haustoria is restored when the host and parasite roots are forced to grow closely together, suggesting that the haustorial hairs play a role in stabilizing the host-parasite association. Thus, our study provides genetic evidence for the regulation and function of haustorial hairs in the parasitic plant.